How Balinese Argue - Hobart, Mark (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
The Imaginary of Bali as paradise stands in stark contrast to what is actually going on. To understand the split requires examining who is authorized to represent Bali as what under what conditions. The issue concerns the nature of argument – whether argumentation and disagreement – and how it disarticulates and marginalize alternatives. The preferred, hegemonic style of argument in Bali is monologue, favoured by those in power, which effectively anticipates and prevents contradiction. By contrast, dialogue is open, democratic and widespread in daily life, but often passes relatively unnoticed. Whereas dialogue enables discussion and problem-solving, monologue re-asserts ideology in the face of uncomfortable actualities. In Bali, the form ideology takes centres on fantasies about an imaginary ‘age-old culture’. The drawbacks are evident in how claims over the cultural antiquity of Tri Hita Karana disguise its grave shortcomings in practice.